2012
DOI: 10.1021/ie3010594
|View full text |Cite
|
Sign up to set email alerts
|

Design, Polymerization, and Properties of High-Performance Seed-Oil-Derived Lubricants

Abstract: There is a significant amount of interest and research in seed-oil-derived lubricants because of elevated environmental consciousness among producers and consumers. While slowly making inroads into selected applications, performance deficits at low temperature and poor thermooxidative stability have consistently relegated seed oil derivatives to roles where biodegradability is paramount or where the performance requirements are relatively low. In this article, the structural attributes that result in seed-oil-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Suresh et al developed two different pathways to synthesize polyurethane polyols from cardanol . Sonnenschine et al used canola or high oleic sunflower oils in addition to soybean oil to produce methyl esters, which were transformed to polyol ester subsequently . Petrovic et al examined ozonolysis to prepare primary polyols from canola and soybean oils, Javni et al studied the effect of isocyanates on soybean oil based polyols, Zlatanic et al tested the effect of structure of vegetable oils on polyols and polyurethanes .…”
Section: Introductionmentioning
confidence: 99%
“…Suresh et al developed two different pathways to synthesize polyurethane polyols from cardanol . Sonnenschine et al used canola or high oleic sunflower oils in addition to soybean oil to produce methyl esters, which were transformed to polyol ester subsequently . Petrovic et al examined ozonolysis to prepare primary polyols from canola and soybean oils, Javni et al studied the effect of isocyanates on soybean oil based polyols, Zlatanic et al tested the effect of structure of vegetable oils on polyols and polyurethanes .…”
Section: Introductionmentioning
confidence: 99%
“…All of these characteristics also depend on the kinetics of the reaction, polydispersity and the method of polyol preparation [35]. Sonnenschein et al found that reactants from seed oil are more useful when triglycerides are separated into fatty acid methyl esters, saturated components are removed and ole n components are properly functionalised [38]. With the seed oil obtained from genetically modi ed plants, it is possible to achieve a high proportion of oleic fatty acid and a small proportion of saturated components.…”
Section: Polyurethanes From Renewable Resourcesmentioning
confidence: 99%
“…With the seed oil obtained from genetically modi ed plants, it is possible to achieve a high proportion of oleic fatty acid and a small proportion of saturated components. For this reason, the aforementioned method seems both economically and practically reasonable [38]. Monomers were obtained through the hydroformylation of oleic methyl esters into corresponding aldehydes, which were hydrogenated to primary alcohols.…”
Section: Polyurethanes From Renewable Resourcesmentioning
confidence: 99%
“…Before development of new natural gas sources, there was vigorous research and development of seed‐oil derived alternatives to petrochemicals feedstocks . While there has been commercial activity substituting seed‐oil derivatives in consumer products, property deficits encountered using naturally derived components have tamped down supply and demand . A potential way to mitigate property deficits using seed‐oil feedstocks is to blend them with conventional petrochemically derived materials possessing more acceptable performance profiles .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] While there has been commercial activity substituting seed-oil derivatives in consumer products, property deficits encountered using naturally derived components have tamped down supply and demand. 5,6 A potential way to mitigate property deficits using seed-oil feedstocks is to blend them with conventional petrochemically derived materials possessing more acceptable performance profiles. 7,8 This approach is based on the concept that negative attributes can be hidden or balanced in such a way that performance is satisfactory for specific applications.…”
mentioning
confidence: 99%